Pengaruh Desain Kolam Terhadap Kecepatan Pertumbuhan Ikan Nila pada Sistem Budidaya Intensif - Beriman Gulo; Irfan Waruwu (Asosiasi Riset Ilmu Tanaman Dan Hewani Indonesia, 2025)
Cultivating tilapia (Oreochromis niloticus) is one of the activities that is widely carried out in Indonesia because this fish has increasing market demand. In intensive cultivation systems, the factor that plays an important role in increasing production yields is pond design. Good pond design can influence water quality, oxygen distribution, and fish comfort which is directly related to fish growth. This research aims to examine the effect of pond design on the growth rate of tilapia in intensive cultivation. Based on a literature review, optimal pond design can increase the efficiency of feed use, maintain good water quality, and create an environment that supports faster fish growth rates. Designs that include pond shape, depth, aeration system and waste management must be carefully considered so that tilapia cultivation can achieve maximum results.